Analisis Seleksi Penerimaan Karyawan Bank Menggunakan Metode Simple Additive Weighting (SAW) dan Pembobotan Rank Order Centroid (ROC) - Naibaho, Sri Fitriani; Bangun, Budianto; Masrizal, Masrizal (Building of Informatics, Technology and Science (BITS), 2025)
This study aims to improve the efficiency and effectiveness of the employee recruitment selection process at Bank BRI Aek Kanopan. The main problem faced is the lack of transparency and systematicity in decision making, so an objective approach is needed to determine the best candidate. As a solution, this study uses the Simple Additive Weighting (SAW) method, which allows structured weighting of criteria, such as last education, technical skills, work experience, communication skills, and age. The SAW method is applied to normalize data and compare candidates based on preference values ​​(Vi). This study involved 25 alternative candidates as evaluation objects, with the normalization and weighting process carried out based on predetermined criteria. The normalized data are presented in a table, with preference values ​​ranging from 0.667 to 0.793, which indicates the level of suitability of candidates to the selection criteria. The results of the study indicate that the SAW method is effective in determining the best candidates, increasing transparency, and facilitating decision making by management. Based on these findings, Bank BRI Aek Kanopan is advised to adopt the SAW method routinely, train staff involved in the selection process, and conduct periodic evaluations to maintain the effectiveness of this method. This research provides an important contribution in the development of human resource management, especially in improving the efficiency and accuracy of the employee recruitment selection process.